Pengaruh Budaya, Tren dan Perilaku Konsumen Terhadap Niat Pembelian Produk Fashion Online di Zalora - Komang Ayu Krisnu Dania Murti; Ni Made Taman Sari; A. A. Sri Purnami (Universitas Warmadewa, 2023)
Research conducted which has gaps in previous research which has differences in previous research. Which aims to be able to test on all the research titles that have been done. As well as being carried out for consumers who can make online purchases on zalora in accordance with a sample of 96 taken using a purposive sampling method using the lemeshow formula. As well as using multiple linear to be able to get all the results for the test results. As well as research results to show answers 1) culture, trends and consumer behavior get positive answers. 2) while culture gets positive results, this means that the better the culture, the higher the purchase intention. 3) and according to the trend obtains positive results, this further increases the trend, the higher the purchase intention. 4) and consumer behavior gets positive answers and the better the consumer behavior, the higher the purchase intention.